Developing Paragraph Writing Material using Skill and Entrepreneurship-based Learning Model - Farikah Farikah (Universitas Muhammadiyah Semarang, 2017)
This study aims to know the teaching materials applied by the lecturers of paragraph writing class, the qualities of the materials, and to what extent the students need paragraph writing materials that are based on skill and entrepreneurship. This research and development approach was intended to develop paragraph writing material using skill and entrepreneurship-based Learning Model. The subject of this research was the fourth semester students of English Department, Tidar University. This research was conducted in three phases. The first was the exploration phase which consists of evaluating the existing of paragraph writing materials. The second was the prototype development phase where the prototype model was developed. The last was testing phase. The results of the research indicated that the paragraph writing material using skill and entrepreneurship-based learning model was needed. It is in accordance with Tidar University vision as entrepreneurship-based university. These findings recommended that skill and entrepreneurship-based learning model could be adopted for developing paragraph writing material.